Scribal Harmonization in the Synoptic Gospels - Pardee, Cambry. (New Testament Tools, Studies and Documents, 2019)
In Scribal Harmonization Cambry G. Pardee examines the earliest Greek manuscripts of the Synoptic Gospels for evidence that scribes altered the text of the Gospels-either deliberately or inadvertently-in ways that eliminated discrepancies between them. The phenomenon of harmonization demonstrates that a scribe's memories of previous experiences with gospel traditions could have a powerful effect on the manuscripts that they produced. This book assembles for the first time a catalogue of harmonizing variants from every manuscript of Matthew, Mark, and Luke from the fourth century and earlier. Far from reducing the unique voices of the individual evangelists to a single melody, the earliest scribes contributed new tones, innovative strains, and fascinating harmonies to the four-fold gospel tradition.